Adjectival Collocations of The Word Bali in The Western Movies: Evidence from Three Corpora - Gusti Ayu Praminatih; Dika Pranadwipa Koeswiryono (Balai Bahasa Provinsi Bali, 2023)
Adjectival collocation could depict the representation of things, such as place and individuals, i.e., a particular group, ethnicity, or community. While extensive studies on adjectival collocation and representation have been conducted in the Western context, only a few studies exist to explore a specific place in Southeast Asia. Consequently, this study aims to explore the adjectival collocation and representation of the word Bali from the Western perspective through its movies. To achieve the study’s objectives, a corpus linguistics approach was applied by utilizing three English corpora: The TV Corpus (TV), The Movie Corpus (Movies), and the Corpus of American Soap Opera (Soap), where the highest adjectival collocations from each corpus were collected to scrutinize context and representation. The findings of this study revealed that the adjectival collocations of the three corpora demonstrated five critical representations of the word Bali in Western movies: tourism, religion, history, terrorism, and crime. Further, the adjectival collocation of the word Bali represented the island as an exotic tourist destination with unique local beliefs and a long history. The word Bali was also represented to experience terrorist attacks and drug smuggling cases that made headlines nationally and internationally. The representations of the word Bali in Western movies adhered to events that significantly affected the island. AbstrakKolokasi adjektiva dapat menggambarkan representasi suatu hal, seperti tempat dan orang, yang terdiri atas kelompok, etnis, atau komunitas tertentu. Meskipun studi ekstensif mengenai kolokasi adjektiva dan representasi telah dilakukan dalam konteks Barat, hanya sedikit studi yang mengeksplorasi suatu tempat tertentu di Asia Tenggara. Oleh karena itu, penelitian ini bertujuan untuk mengeksplorasi kolokasi adjektiva dan representasi kata Bali dari sudut pandang Barat melalui film. Untuk mencapai tujuan penelitian, pendekatan linguistik korpus diterapkan dengan menggunakan tiga korpora bahasa Inggris: TV Corpus (TV), The Movie Corpus (Movies), dan Corpus of American Soap Opera (Soap). Kolokasi adjektiva tertinggi dari tiap-tiap korpus dikumpulkan untuk meneliti konteks dan representasi. Temuan dari penelitian ini mengungkapkan bahwa kolokasi adjektiva dari ketiga korpora tersebut menunjukkan lima representasi kritis dari kata Bali dalam film Barat: pariwisata, agama, sejarah, terorisme, dan kriminalitas. Kolokasi adjektiva dari kata Bali merepresentasikan pulau ini sebagai tujuan wisata eksotis dengan kepercayaan lokal yang unik dan sejarah yang panjang. Selanjutnya, kata Bali juga direpresentasikan mengalami serangan teroris dan kasus penyelundupan narkoba yang menjadi berita utama secara nasional dan internasional. Representasi kata Bali dalam film Barat sejalan dengan peristiwa yang secara signifikan mempengaruhi pulau ini.